Telomere length and the risk of cardiovascular diseases: A Mendelian randomization study - Deng, Yingjian; Li, Qiang; Zhou, Faguang; Li, Guiyang; Liu, Jianghai; Lv, Jialan; Li, Linlin; Chang, Dong (Frontiers in Cardiovascular Medicine, 2022)
Background The causal direction and magnitude of the associations between telomere length (TL) and cardiovascular diseases (CVDs) remain uncertain due to susceptibility of reverse causation and confounding. This study aimed to investigate the associations between TL and CVDs using Mendelian randomization (MR). Materials and methods In this two-sample MR study, we identified 154 independent TL-associated genetic variants from a genome-wide association study (GWAS) consisting of 472,174 individuals (aged 40–69) in the UK Biobank. Summary level data of CVDs were obtained from different GWASs datasets. Methods of inverse variance weighted (IVW), Mendelian Randomization-Egger (MR-Egger), Mendelian Randomization robust adjusted profile score (MR-RAPS), maximum likelihood estimation, weighted mode, penalized weighted mode methods, and Mendelian randomization pleiotropy residual sum and outlier test (MR-PRESSO) were conducted to investigate the associations between TL and CVDs. Results Our findings indicated that longer TL was significantly associated with decreased risk of coronary atherosclerosis [odds ratio (OR), 0.85; 95% confidence interval (CI), 0.75–0.95; P = 4.36E-03], myocardial infarction (OR, 0.72; 95% CI, 0.63–0.83; P = 2.31E-06), ischemic heart disease (OR, 0.87; 95% CI, 0.78–0.97; P = 1.01E-02), stroke (OR, 0.87; 95% CI, 0.79–0.95; P = 1.60E-03), but an increased risk of hypertension (OR, 1.12; 95% CI, 1.02–1.23; P = 2.00E-02). However, there was no significant association between TL and heart failure (OR, 0.94; 95% CI, 0.87–1.01; P = 1.10E-01), atrial fibrillation (OR, 1.01; 95% CI, 0.93–1.11; P = 7.50E-01), or cardiac death (OR, 0.95; 95% CI, 0.82–1.10; P = 4.80E-01). Both raw and outlier corrected estimates from MR-PRESSO were consistent with those of IVW results. The sensitivity analyses showed no evidence of pleiotropy (MR-Egger intercept, P > 0.05), while Cochran’s Q test and MR-Egger suggested different degrees of heterogeneity. Conclusion Our MR study suggested that longer telomeres were associated with decreased risk of several CVDs, including coronary atherosclerosis, myocardial infarction, ischemic heart disease, and stroke, as well as an increased risk of hypertension. Future studies are still warranted to validate the results and investigate the mechanisms underlying these associations.